2006
DOI: 10.1002/jor.20066
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term microvascular response of striated muscle to cp‐Ti, Ti‐6Al‐4V, and Ti‐6Al‐7Nb

Abstract: Due to excellent mechanical properties and good corrosion resistance, titaniumaluminium-vanadium (Ti-6Al-4V) and titanium-aluminium-niobium (Ti-6Al-7Nb) are extensively used for orthopedic surgery. Concern has been voiced concerning the implications of the constituent vanadium in Ti-6Al-4V on the surrounding environment. Particularly in osteosynthesis where the alloys stand in direct contact to skeletal muscle, undesirable biologic reactions may have severe consequences. In a comparative study, we assessed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 39 publications
0
16
0
1
Order By: Relevance
“…Shimajo et al reported that human gingival fibroblasts similarly adhered, spread, and proliferated on Ti-6Al-7Nb and cpTi. In addition, shortterm in vivo implantation resulted in a transient inflammation response to Ti-6Al-7Nb that resembled the response to cpTi, with no obvious adverse biological effects (11,12). Our group previously reported that Ti-6Al-7Nb promoted better osteoblast-like cell spreading as compared with cpTi (13).…”
Section: Introductionmentioning
confidence: 75%
“…Shimajo et al reported that human gingival fibroblasts similarly adhered, spread, and proliferated on Ti-6Al-7Nb and cpTi. In addition, shortterm in vivo implantation resulted in a transient inflammation response to Ti-6Al-7Nb that resembled the response to cpTi, with no obvious adverse biological effects (11,12). Our group previously reported that Ti-6Al-7Nb promoted better osteoblast-like cell spreading as compared with cpTi (13).…”
Section: Introductionmentioning
confidence: 75%
“…Ti-6Al-4V activates monocytes and induces the release of the inflammatory mediator prostaglandin E2, IL-1, TNF-α, and IL-6 to a greater extent than Ti-6Al-7Nb [142]. In an in vivo study Ti-6Al-7Nb and cpTi induced slightly less inflammation than Ti-6Al-4V while both showed slight increase of microvascular permeability [143]. It was also declared that Ti- 6Al-4V particles implanted into the murine air pouch-model caused a reactive membrane inflammation, probably mediated by IL-6 [144].…”
Section: Methodsmentioning
confidence: 99%
“…23 Pennekamp et al reported that Ti-6Al-7Nb lowered the inflammatory response, which was analogous to pure Ti. 24 Interestingly, our results showed that the alkaline phosphatase activity on Ti-6Al-7Nb surfaces was much higher than that on pure Ti surfaces, which may attribute to the niobium element. 25 Our results have shown that the hierarchical micro/ nanotopographies of Ti-6Al-7Nb alloy were biocompatible on the functions of BMSC in vitro.…”
Section: Discussionmentioning
confidence: 85%